STATUS ANAK DAN HARTA BENDA AKIBAT PERKAWINAN CAMPURAN ANTARA WARGA NEGARA INDONESIA DAN WARNA NEGARA BELANDA. - Sintya Irawati (Universitas 17 Agustus 1945 Samarinda, 2019)
AbstractThe general public's understanding of mixed marriages is still very minimal, especially regarding the legal consequences that have arisen after the implementation of mixed marriages. This thesis discusses the effects of mixed marriages on the status of children and property acquired after mixed marriages especially those that occur in Indonesian citizens and Dutch citizens. This research is descriptive in nature which refers to a legal comparison between Indonesia and the Netherlands regarding mixed marriages. The comparison are examined in terms of marital law and citizenship in force in both countries. The countries of Indonesia and the Netherlands have rules regarding mixed marriages and their respective nationalities so it is very interesting to discuss. The source of law in Indonesia is still very much adhering to the Dutch Law Source so that the rules of the two countries are not much different. The results of this study aim to educate the general public and especially mixed marriages between Indonesian citizens and Dutch citizens.